The analysis of water injection systems in sandstone hydrocarbon reservoirs, case study from the western part of the Sava Depression (Rudarsko-geološko-naftni zbornik, 2016)
Formation water injection is one of the constituent parts of the hydrocarbon production cycle in the secondary exploitation oil recovery phase. The formation water injection system can be divided the into single and central injection systems. The formation water injection costs have been described in this paper using the examples of fi eld A (central injection system) and fi eld B (single injection system). These are located in the western part of the Sava Depression. The reservoir rocks regarding the oil and gas fi elds A and B are fi ne to middle grained sands and quartz micaceous sandstones that belong to the geological age of Lower Pontian. The average porosity (intergranular) in fi eld A is 15–35% and in fi eld B it is 10-31%, depending on the depth and cementation percentage. Regarding the oil and gas fi elds described in this paper, a cost comparison has been made and an injection system sensitivity analysis as well as an analysis of possible injection systems’ costs for optimization and rationalization.